AVALIAÇÃO DE IMPACTO DE POLÍTICAS PÚBLICAS: uma experiência com o Projeto Inverno Gaúcho da Secretaria da Saúde do Estado do Rio Grande do Sul - Marília Patta Ramos (Universidade Federal do Maranhão, 2010)
This article refers to an experience related to a policy evaluation. Specifically it is presented the evaluation of a project developed by the Rio Grande Health Secretary: the Inverno Gaucho Project, which intends to reduce the hospitalization of children under 5 years of age due to respiratory infections. This evaluation was done with counties that participated in the project in comparison to those counties that didn't participate in it. The use of a comparative group of counties that didn't participate in the considered policy was necessary to control characteristics that can affect the hospitalization of children due to respiratory infection rates (dependent variable) that were not related to the project. In terms ofthe analytical procedures used descriptive analysis were done to compare means and also multivariate regression models were run to estimate the dependent variable. It was observed thatthe greatest mean difference among participants and non participants happened during the year 2008. And, this difference pointed out that participants presented lower hospitalization due to respiratory infection than those non participants.